Semiotic Analysis of Sampoerna a Mild Image Creation - Regina Siddharta (Institute of Research and Community Outreach - Petra Christian University, 2019)
This thesis mainly deals with the process of signification in order to find out what images are being built, how those images are represented, and what messages delivered in Sampoerna A Mild billboard advertisements through the use of semiotic resources. The focus of the writers’ analysis is the advertisements themselves, as the writer uses the process of signification that involves denotation, connotation, and myth. Those theories help the writers in analyzing the meaning of the advertisement first, and then figure out how meaning is created by the advertisement. Meaning in this research is an integrated form consisting the meaning from three level of signification process: denotative level, connotative level, and myth. This research uses qualitative content analysis method to describe the meaning of qualitative materials in a systematic way. At the end, those denotative meaning and connotative meaning build an image and create myth which naturalizes the image itself. Key Words: billboard advertisements, sampoerna a mild, semiotics, process of signification, connotation, denotation